Tercería de propiedad y procesos judiciales de múltiples reclamantes en el juzgado civil de Maynas 2023 - Salgado Díaz, Luis Miguel Angel (2025)
The research addresses the application of the third-party property claim in the Civil Court of Maynas, aiming to analyze its relationship with judicial processes. This study focuses on identifying the barriers present in its implementation and how they affect the protection of property rights. The research is quantitative and correlational in nature, with a non-experimental design, and analyzes a sample of 80 respondents. The results show a significant correlation (Rho = 0.689) between the application of the third-party property claim and the perception of judicial processes in Maynas, indicating that the proper application of the third-party property claim contributes to a greater perception of effectiveness in these processes. Concerns were also found regarding inconsistent judicial interpretation and excessive documentary requirements, which hinder the mechanism's effectiveness, as a significant percentage of respondents (45%) expressed reservations about its application. Additionally, the dimension of property ownership was analyzed, where 68.8% of respondents support the recognition of ownership rights, while 31.3% disagreed, suggesting the need to improve consistency in its application. Regarding the exclusion of the debtor’s rights, although 55% agree, 45% disagreed, highlighting the need for a deeper review of the impact of this measure on the debtor's rights. The analysis also reveals that the dimension of better right generated significant disagreement (47.6%), indicating that the lack of clarity in its application creates legal uncertainty among participants. Finally, the research emphasizes the importance of improving the effectiveness of due process and effective judicial protection in these cases, as 26.3% expressed doubts about the efficiency of the judicial system in these processes.